2010
DOI: 10.1007/s12663-010-0092-x
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Presentation of Caustic Ingestion and its Surgical Treatment: A Case Report

Abstract: Treatment and reconstruction of oral scar contracture, is always a challenging procedure to restore structure and functions of the oral cavity. We present a case of a patient with limited mouth opening who sustained extensive oral scar contracture with complete adhesion of tongue to floor of mouth following ingestion of caustic soda without his knowledge 4 years back. We performed a surgical release of the scar contractures from buccal mucosa on both sides, along with a release of the tongue from the floor of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Oral cavity injuries caused by caustic ingestion, including microstomia, shallow vestibule, ankyloglossia, speech impairment, loss of teeth and impairment in facial expression have been reported in the literature [2][3][4] . We present a case of scar contracture between the tongue and mouth floor with stone formation in the submandibular salivary duct.…”
Section: Introductionmentioning
confidence: 99%
“…Oral cavity injuries caused by caustic ingestion, including microstomia, shallow vestibule, ankyloglossia, speech impairment, loss of teeth and impairment in facial expression have been reported in the literature [2][3][4] . We present a case of scar contracture between the tongue and mouth floor with stone formation in the submandibular salivary duct.…”
Section: Introductionmentioning
confidence: 99%
“…Caustic ingestions are among the most prevalent causes of toxic exposure [1]. Accidental caustic ingestion is most common in children with intentional ingestion and attempted suicide, common in adolescents and adults [1].…”
Section: Introductionmentioning
confidence: 99%
“…Caustic ingestions are among the most prevalent causes of toxic exposure [1]. Accidental caustic ingestion is most common in children with intentional ingestion and attempted suicide, common in adolescents and adults [1]. It has been reported that a number of patients who ingest caustic substances have accompanying psychiatric disorders [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation